Pengaruh Lokasi Dan Citra Merek Terhadap Keputusan Pembelian Jasa Kamar Di Unp Hotel & Convention Center - Ziana Sastia; Youmil Abrian (Departemen Pariwisata Universitas Negeri Padang, 2025)
This research is motivated by location and brand image on the decision to purchase room services at UNP Hotel & Convention Center. The purpose of this study is to analyze the effect of location and brand image on the decision to purchase room services. Research using descriptive with quantitative data. The types used are primary and secondary data. The population of this research is guests who come to UNP Hotel & Convention Center. In this study, the Hair Technique was used with the number of items being 15 question items used to measure 3 variables, so the number of respondents used was 15 question items multiplied by 10 equaling 150 respondents. The survey method uses a questionnaire (questionnaire) with a Likert scale which is checked for validity and reliability. Data from this study were processed using SPSS 25.00. The results of this study indicate that the location is in a fairly good category, namely 45.34%. Furthermore, the brand image variable is in a fairly good category, namely 48%, and the purchase decision variable is in a fairly good category, namely 47.33%. Location (X1) and brand image (X2) on purchasing decisions (Y). with a score of 57.3% and 42.75% influenced by several other factors. The results of multiple linear regression analysis obtained an F count of 101,087 with sig. 0.000 <0.05, meaning that the location and brand image variables have a significant effect on the purchasing decision variable, and the t count value is 5,826 on the location variable and t count is 5,479 on the brand image variable with sig. 0.000 < 0.05.